CHALLENGES FACED BY ART AND TECHNOLOGY ON SOCIAL AND ETHICAL GROUNDS - DHUNNA, MANINDER SINGH; Singh, Garima (International Journal of Research -GRANTHAALAYAH, 2021)
The use of technologies in art is at its peak and it wouldn't be wrong to state that the blend of technology and art has become the strongest factor for shaping the educational and artistic landscape. From reviving modern art, technology acts as an influential path for artists to create something unique. Different genres of art also merge with technology and give rise to pieces of work that reflect exclusiveness. It offers a powerful connection paralleled with human endeavor. These digital technologies instill smart thinking, smart concepts, and methods of creation in artists. However, the study explores the challenges faced by art and technology in terms of social and ethical platforms. To study the challenges faced by art and technology, we will also discuss opportunities it provides to artists and the art industry. To address the research paper, the study adopts a quantitative method to answer the research objectives